Senegal : Progress Report on Implementation of the PRSP 2003 Summary. (IMF Staff Country Reports; Country Report ;, 2005)
This progress report on Senegal's Poverty Reduction Strategy Paper (PRSP) highlights that tax collection has been found to be effective as it attained the level foreseen in the high case scenario despite less favorable mobilization of PRSP resources than expected. More public investment expenditures have been financed with internal resources than the intermediate case scenario predicted. The wage bill held steady at 30.1 percent of revenue, which is 1 percent more than the PRSP scenario figures.